2017
DOI: 10.1016/j.clinbiomech.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic femoral head translations in dysplastic hips

Abstract: 2017-08-25T16:29:20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
(46 reference statements)
3
12
0
Order By: Relevance
“…Thus, the motion of the joint approximates a pure ball-and-socket joint in these positions. This finding is consistent with the results of Sato et al, 34,35 who reported that during walking (peak flexion angle, approximately 35°), the superior-inferior component of femoral head translation was within 0.5 mm. Similarly, Akiyama et al 3 showed that from neutral to 15° of extension, theindividual components were between 0.15 mm and 0.57 mm, with the 3-dimensional resultant translation <0.86 mm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the motion of the joint approximates a pure ball-and-socket joint in these positions. This finding is consistent with the results of Sato et al, 34,35 who reported that during walking (peak flexion angle, approximately 35°), the superior-inferior component of femoral head translation was within 0.5 mm. Similarly, Akiyama et al 3 showed that from neutral to 15° of extension, theindividual components were between 0.15 mm and 0.57 mm, with the 3-dimensional resultant translation <0.86 mm.…”
Section: Discussionsupporting
confidence: 93%
“…16,20,32,36 Moreover, little detailed information exists defining the normal motion of the hip during functional activities, especially at the resolution required to separate physiologic from pathologic motion, which previous studies of labral mechanics showed to occur at the submillimeter level. 28,34,35 In view of this absence of fundamental information concerning the kinematics of the hip and the contribution of the joint capsule, we performed an experimental study to answer the following questions:…”
mentioning
confidence: 99%
“…The findings in this study should be interpreted with the understanding that these limitations may significantly bias the results. However, this cohort is similar to that in previous hip kinematic studies (eight healthy and twelve DDH hips [44], eight [45] or eleven [46] replaced hips) due to the demanding study protocol with radiographic surveillances, CT scans, and density-based image-matching techniques, and is consistent with minimizing X-ray exposure to individuals, and the studies nevertheless obtained important information. Second, we only evaluated the kinematics of the hip joint during a squatting.…”
Section: Discussionsupporting
confidence: 84%
“…The hip is subjected to distraction forces throughout most activities of daily living, with fluoroscopic evidence of hip subluxation during the swing phase of gait. 8,18,19,31 Resultant instability from an incongruent capsule may lead to an increased incidence and degree of subluxation, which can accelerate joint damage and result in poor outcomes. 29,39 Arthroscopic capsular reconstruction should therefore be considered for patients with irreparable capsular defects to significantly improve hip distractive stability.…”
Section: Discussionmentioning
confidence: 99%
“…2,14,30,36 The role of the capsule in maintaining distractive stability of the hip (ie, the hip’s ability to resist distractive force) has yet to be elucidated, despite the fact that the hip joint is subjected to distractive forces throughout activities of daily living. 8,18,19,31 Repetitive subluxation and joint instability have been cited as factors for accelerated joint degeneration and revision surgery. 29,39 To the authors’ knowledge, no biomechanical study has investigated distractive stability in the capsular reconstruction state.…”
mentioning
confidence: 99%